Mortality and Cardiovascular End Points In Relation to the Aortic Pulse Wave Components: An Individual-Participant Meta-Analysis - Norton Gavin R.; An De-Wei; Aparicio Lucas S.; Yu Yu-Ling; Wei Fang-Fei; Niiranen Teemu J.; Liu Chen; Stolarz-Skrzypek Katarzyna; Wojciechowska Wiktoria; Jula Antti M.; Rajzer Marek; Martens Dries S.; et al. (Lippincott, 2025)
Background: Wave separation analysis enables individualized evaluation of the aortic pulse wave components. Previous studies focused on the pressure height with overall positive but differing results. In the present analysis, we assessed the associations of the pressure of forward and backward (Pfor and Pref) pulse waves with prospective cardiovascular end points, with extended analysis for time to pressure peak (Tfor and Tref).
Methods: Participants in 3 IDCARS (International Database of Central Arterial Properties for Risk Stratification) cohorts (Argentina, Belgium, and Finland) aged ≥20 years with valid pulse wave analysis and follow-up data were included. Pulse wave analysis was done using the SphygmoCor device, and pulse wave separation was done using the triangular method. The primary end points consisted of cardiovascular mortality and nonfatal cardiovascular and cerebrovascular events. Multivariable-adjusted Cox regression was used to calculate hazard ratios.
Results: A total of 2206 participants (mean age, 57.0 years; 55.0% women) were analyzed. Mean±SDs for Pfor, Pref, Tfor, and Tfor/Tref were 31.0±9.1 mm Hg, 20.8±8.4 mm Hg, 130.8±35.5, and 0.51±0.11, respectively. Over a median follow-up of 4.4 years, 146 (6.6%) participants experienced a primary end point. Every 1 SD increment in Pfor, Tfor, and Tfor/Tref was associated with 27% (95% CI, 1.07-1.49), 25% (95% CI, 1.07-1.45), and 32% (95% CI, 1.12-1.56) higher risk, respectively. Adding Tfor and Tfor/Tref to existing risk models improved model prediction (∆Uno's C, 0.020; P<0.01).
Conclusions: Pulse wave components were predictive of composite cardiovascular end points, with Tfor/Tref showing significant improvement in risk prediction. Pending further confirmation, the ratio of time to forward and backward pressure peak may be useful to evaluate increased afterload and signify increased cardiovascular risk.